Gout Arthritis of Temporomandibular Joint - A Rare Case Report and Review of Literature - Nishant Kumar; Kumari Jyotsana; M. Srinivasa Raju; Basavaraj T. Bhagawati (Wolters Kluwer Medknow Publications, 2024)
Gout is a metabolic disorder that leads to elevated serum uric acid levels and deposition of urate crystals in the joints. The disease is usually confined to the joint space and leads to pain and limitation of jaw opening. The case describes a 45-year-old female patient with a chief complaint of 'occasional pain in the left temporal muscle region'. The case disclosed a gout manifestation in the temporomandibular joint (TMJ) after physical and radiographic findings. Gout manifestation in the TMJ is an unusual presentation and a few reports in the English literature address the subject. Gout in the TMJ should be included as a differential diagnosis for joint disorders because of its rarity. A clinician may overlook gout involving the TMJ in the differential diagnosis of facial pain even when the patient has received a diagnosis of gout in other joints.